Issues in Infectious Diseases 2007
DOI: 10.1159/000104246
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Symbiosis in Arthropods

Abstract: Wolbachia pipientis is an intracellular bacteria found within the cytoplasm of a high proportion of arthropods. Widespread in insects, Wolbachia is also commonly found in other arthropod groups, including mites, spiders and terrestrial isopods. Wolbachia are normally maternally inherited and have evolved a number of strategies to ensure transmission. These include: (1) feminization, the conversion of genetic males into females, (2) parthenogenesis, the production of diploid offspring without sexual reproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…Among the most common manipulations are host feminization, parthenogenesis induction, male killing and cytoplasmic incompatibility (CI) (Werren, 1997;Stouthamer et al, 1999) as well as other, sometimes subtle, effects on hosts (Clark, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common manipulations are host feminization, parthenogenesis induction, male killing and cytoplasmic incompatibility (CI) (Werren, 1997;Stouthamer et al, 1999) as well as other, sometimes subtle, effects on hosts (Clark, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ferree & Sullivan (2006) excluded the possibility that the maternal pronucleus is involved in CI induction by an elegant genetic test using a combination of an androgenetic mutant and interspecies mating between D. melanogaster females and Wolbachia ‐infected D. simulans males. These results are consistent with previous cytological studies in Drosophila and Nasonia showing that CI induction occurs by paternal pronucleus modification (Tram et al ., 2003; Clark, 2007). However, no detailed genetic studies have yet been reported to elucidate rescue mechanisms in infected eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular basis of CI is not yet known, cytological studies have described comparable defects associated with CI during early embryonic development in flies (Lassy & Karr, 1996;Callaini et al, 1997;Clark et al, 2005), parasitoid wasps (Tram & Sullivan, 2002;Tram et al, 2006) and woodlice (Moret et al, 2001). Incompatible embryos commonly show paternal chromosome condensation failure and abnormal segregation in the first mitotic division, leading to embryonic death (Tram et al, 2003;Clark, 2007). Analysis of the genome sequence of a CI-inducing Wolbachia strain of Drosophila melanogaster, wMel, (Wu et al, 2004) has identified a number of genes that might be involved in host interaction, including an unusually high number of genes that encode proteins containing ankyrin repeat (ANK) domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be relevant that the Wolbachia within these filarial species cluster with arthropod Wolbachia in supergroup F, and that a relatively recent transfer of Wolbachia between these arthropod and nematode species is indicated (Casiraghi et al 2005 ). The apparent lack of complete saturation of Wolbachia in these few nematode species may therefore reflect a more recent arthropod origin where parasitism generally prevails (Werren 1997 ; Clark 2007 ). Conceivably, Wolbachia do not form an obligate mutualism in those filarial species that appear to contain both infected and uninfected worms.…”
Section: Is the Symbiotic Relationship Between Wolbachia mentioning
confidence: 99%